The expression profiles and roles of microRNAs in cardiac glucose metabolism - Shen, Nan-Nan; Qian, Hua; Zhu, Ya-Fang (Frontiers in Endocrinology, 2025)
BackgroundMicroRNAs (miRNAs) are a class of endogenous, non-coding RNAs, that have been implicated in cardiovascular diseases. Recent studies have suggested that dysregulated miRNAs accumulate in the heart and may be associated with impaired cardiac glucose metabolism. However an inconsistent direction of expression was observed in the current available literature. The aim of this study was to characterize miRNA expression profiles associated with glucose metabolism, and to explore their potential as biomarkers for glucose metabolism disorders in diabetic cardiomyopathy (DCM).MethodsA systematic search of electronic databases, including Embase, PubMed, and the Cochrane Library, was conducted until October 1, 2024. Studies reporting on miRNAs expression profiles that regulate glucose metabolism in the heart were selected for inclusion. Pooled results were presented as log10 odds ratios (logORs) with 95% confidence intervals (CIs), using random-effect models. Subgroup analyses were conducted based on species, region, and sample source. Analyses by species focused specifically on humans and mice. The quality of included articles was assessed using the modified Diagnostic Accuracy Study 2 (QUADAS-2) tool. All workflows, including abstract screening, full-text review, data extraction, and quality assessment, were independently performed by two reviewers.ResultsA total of 47 eligible articles were included in this study, identifying 70 dysregulated miRNAs. Further analysis revealed that compared with the non-DCM group, the DCM group exhibited differential miRNA expression, with 12 miRNAs consistently upregulated and 8 consistently downregulated. Among these miRNAs, miR-199a (logOR 4.59; 95% CI: 3.02-6.15) was the most upregulated and frequently reported (n=7 studies), while let-7 (logOR 4.48; 95% CI: 2.41-6.55) was the most downregulated (4 studies). Subgroup analysis indicated that miRNA-21 was the most upregulated in cardiac tissue, and miRNA-133 was the most downregulated in cardiomyocytes. Additionally, miRNA-21 was found to be the most upregulated across different species. In the region subgroups, miRNA-199a and miRNA-503 were the most upregulated and downregulated in Asian countries, whereas miRNA-378 was the most dysregulated in non-Asian countries.ConclusionIn summary, this study identified 20 consistently dysregulated miRNAs assocaited with myocardial glucose metabolism. Six dysregulated miRNAs, including miRNA-199a, let-7, miRNA-21, miRNA-133, miRNA-503 and miRNA-378, have potential as candidate miRNA biomarkers of glycometabolism in the heart. These findings require further validation in future larger-scale studies.